Incidence and prevalence of pulmonary arterial hypertension associated with systemic lupus erythematosus. A systematic review - Vadim D. Zakiev; Tamila V. Martynyuk; Yulia V. Kotovskaya (LLC "MEDIAFORMAT", 2024)
Relevance. Pulmonary arterial hypertension (PAH) is a rare complication of systemic lupus erythematosus (SLE). Due to the nonspecificity of symptoms and difficulties in diagnosis, the exact incidence and prevalence of PAH associated with SLE is unknown. Aim. A systematic review of studies assessing the incidence and prevalence of PAH associated with SLE. Material and methods. A systematic search was performed for studies investigating the incidence and prevalence of PAH associated with SLE published from January 1, 2000 to December 31, 2023. The search was carried out in the PubMed/MEDLINE database for English-language publications and in the RSCI database for studies in Russian according to pre-defined inclusion and exclusion criteria. Results. 53 potential publications were identified, all sources in English. 11 publications remained for further assessment after screening article titles and abstracts. After detailed analysis, 6 articles were excluded because they did not meet the inclusion and exclusion criteria. Totally, 5 studies were included in the systematic review. Three studies assessed prevalence only, one study assessed incidence only, and one study assessed both prevalence and incidence. The prevalence of PAH associated with SLE ranged from 0 to 4.2%, with 3-year and 5-year cumulative incidence rates of 0.53-1.2% and 0.77-1.8%, respectively. Conclusion. A systematic review showed a low prevalence and incidence of PAH associated with SLE.